Aesthetic thought in pragmatic philosophy (Journal of the College of Basic Education, 2023)
The peoples who want to find a place for themselves on the map of the earth seek to putScience is in the forefront, as it takes into account the huge amount of scientific and technical development thatIt is described in the light of the mind system by experience and evidence.As a result of the informational and technological expansion and explosion, the scientific view has become a necessity.One of the necessities of civilized and contemporary societies, therefore, it can be asserted that the era of spontaneityAnd randomness has passed, and it has been replaced by the scientific, experimental view of running the course of life in all aspects.fields, and this, of course, does not preclude the entry of this pragmatic thought into the science of art.The nature of facts, perceptions, ideas, meanings, experiences and sensations that ariseThe human burdens and develops through them is the result of accumulating experiences and this progress and communicationIntellectual with the developments of life comes as one of the necessities of pragmatic thought that believes indevelopment and utilitarianism in a way that serves the interest of man, because it is a form of the relationship betweenThe human being as a tool linked to other tools represented by things and people to form a unifying fabricBetween ideas, hypotheses and patterns of behavior in the same community.The principles of pragmatic thought mainly aim at sharing practical experience, and this isIt is reflected in the pragmatic aesthetic thought, which is one of the pillars of the system that looks towards expediency.And satisfy the interests and fill the needs of the organism. The value of the artwork depends on the basison the style of the exhibitor and the possibility of exploiting all the formal possibilities that do not affect or threatenFreedom of creativity and the necessary conditions for the advancement of true artistic work.The connection between pragmatic thought and art is not born of the present.Bridges that adopt science and experimentation as a technology. In the creative process, the artist'smaterialism according to his perception to reach emotion, which is the final result that every artist seeks